PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2010-2012) - Andhika Rahadian; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
The aim of this research to analyze the effect of corporate governance on firms' capital structure. This research uses the annual report documentation on companies listed in Indonesia Stock Exchange ( BEI ) in 2010-2012 . The sampling method used in this study is purposive sampling with specified criteria . The number of samples obtained from these criteria amounted to 102 samples. Hypothesis testing using multiple regression analysis. The results of this research indicate that ownership concentration and managerial ownership are significantly negative  related to capital structure. While other variables such as the size of the board of directors, independent directors, and remuneration  are not significantly effected. This research also uses the control variable and the result is  liquidity and asset tangibility is significantly negative effected to capital structure . While another control variables such as profitability  and firm size are not significantly effected.